2019
DOI: 10.1016/j.jhep.2019.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastography for screening of liver fibrosis: Cost-effectiveness analysis from six prospective cohorts in Europe and Asia

Abstract: Highlights Optimal liver stiffness thresholds for community-based screening in populations with metabolic risk factors and alcoholic is between 9.1 and 9.5 kPa for the diagnosis of significant fibrosis (stages ≥F2)  Transient elastography is a cost-effective intervention for identifying patients with liver fibrosis in primary care. Healthcare systems would need to invest between 2,500 (at-risk population) to 6,500 (general population) purchasing power parity-adjusted euros to gain an extra year of life, adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
1
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 52 publications
(58 reference statements)
2
81
1
6
Order By: Relevance
“…Therefore, validated surrogate scores of advanced fibrosis are used to stage the disease severity. The most accurate non-invasive identification of NAFLD patients with advanced fibrosis has been studied extensively, and in addition to LSM, NAFLD fibrosis score and the FIB-4 index perform best 15,18 ; however, cut-off values to rule out significant fibrosis may vary between different chronic liver diseases and populations. By the use of the recently proposed FIB-4 cut-off (>2.67 for advanced fibrosis), 64%, 26%, and 10% of our cohort were classified to have no significant fibrosis, an indeterminate stage, or advanced fibrosis, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, validated surrogate scores of advanced fibrosis are used to stage the disease severity. The most accurate non-invasive identification of NAFLD patients with advanced fibrosis has been studied extensively, and in addition to LSM, NAFLD fibrosis score and the FIB-4 index perform best 15,18 ; however, cut-off values to rule out significant fibrosis may vary between different chronic liver diseases and populations. By the use of the recently proposed FIB-4 cut-off (>2.67 for advanced fibrosis), 64%, 26%, and 10% of our cohort were classified to have no significant fibrosis, an indeterminate stage, or advanced fibrosis, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A particularity of the German guideline is the implementation of VCTE in the screening algorithm, which was indicated in about 75% of our patients. LSM-based approaches were recently evaluated from a health economics standpoint and found to be potentially cost-saving in populations at risk 41 . However, universal access to this method would require large investments 21 and modifications to the reimbursement system in most European countries, depending on national health care.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our single centre study should be reproduced in a multi-centre approach, ideally in primary care. Such a study should be accompanied by a detailed health-economics analysis to verify potential cost benefits of such screening strategies 41 .…”
Section: Discussionmentioning
confidence: 99%
“…With a rise in recognition of NAFLD, strategies to reduce pressure on secondary services and costs for the health care system will be crucial. A recent evaluation of a large data set (n = 6,295 participants) from Europe and Asia demonstrated that community‐based screening for liver fibrosis with transient elastography was cost‐effective through earlier identification of patients, and the authors suggested that it could represent a valuable public health strategy . However, in the current cohort of patients with NAFLD, availability of transient elastography or the ELF test in primary care centers may not have avoided the need for hepatology referral, as most of the patients (88.5%) were referred with a request for an opinion regarding other clinical concerns.…”
Section: Discussionmentioning
confidence: 99%